Marital Residence Patterns in Late Neolithic Communities of the Vinča Culture - Marko Porčić (University of Belgrade, 2016)
This paper aims to reconstruct the marital residence patterns in late Neolithic communities in the central Balkans. The average size of the habitation site was used as a correlate of patrilocality or matrilocality. A study of the habitation sites of the Vinča culture shows that judgments about marital residence patterns vary between sites and their phases. There are, however, certain indications that patrilocality may be considered the more probable pattern for most of the sites.